PENGENDALIAN SECARA BIOLOGIS PENYAKIT LAYU BAKTERI JAHE DENGAN Streptomyces spp. - , HENDRI BUSTAMAM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bacterial wilt caused by Ralstonia solanacearum is one of the important diseases on ginger in Indonesia. This pathogen is difficult to be controlled by chemical and cultural practices, therefore it is needed to find other alternative controls. Biological control can play an important role in the management of bacterial wilt disease. Healthy ginger rhizosphere in the infected field has several potential microorganisms that suppress wilt pathogen, including the group of Streptomyces. These microbes have not been studied as biological control agents on wilt disease of ginger yet. The research was done to find a potential Streptomyces species that can be used to control this disease. The objectives of this study were to find out effective Streptomyces for controlling bacterial wilt disease on ginger , as well as to evaluate its effect on the plant growth and production of ginger rhizome. It also aimed to characterize the bacterial antagonist (Streptomyces spp.). The study involving several trials i.e. selection of Streptomyces spp., and identification the environmental factors that influencing Streptomyces growth were carried out in the laboratory of Plant Bacteriology and in screen house of Faculty of Agriculture, Gadjah Mada University, Yogyakarta. There were also experiment on selection of Streptomyces spp. in vivo, virulency test of Streptomyces application, and control of bacterial wilt disease on ginger which carried out at farmerâs field in Boyolali, Central Java. Research result showed that Streptomyces spp. isolated from the rhizosphere of ginger as antagonist to R. solanacearum K3 were high physical and physiological variation. Antagonist mechanism was bacteriostatic and bactericidal. Greenhouse screening founded five antagonists, Streptomyces sp. S67, isolated from ginger rhizosphere from Rejang Lebong District, and Streptomyces spp. isolates S57, S59, S42, and S53, from Kaur District, those suppresed the ginger,s wilt disease and promoted the growth and yield of ginger. Temperature 20â37oC, and pH 4.5â9, influenced the growth of Streptomyces spp. but salt content 0â2500 ppm in medium was not. Soaking one hour with Streptomyces sp. S57, concentration at 107 cfu/ml, and adding antagonist after 1 month cultivation, were the best treatment to suppress the ginger wilt disease and promote the growth and yield of ginger in the field.